On the asymptotic topology of groups and spaces. Part I - Otera, Daniele Ettore (Lietuvos matematikos rinkinys, 2014)
This note presents a few basic notions of the topology at infinity of groups and manifolds, from a low-dimensional topological viewpoint. In particular, we will talk about some topological conditions ensuring the tameness of ends of spaces.